3 - L’illusion du e-voting dans les organisations syndicales de Côte d’Ivoire1 : entre légitimité et défis démocratiques - Kouadio, Yao Adoman Francis (Africa Development, 2022)
Based on a qualitative methodology combining field data and documentation, this study aims to understand the social processes of legitimisation of the voting technique at work in trade unions in Côte d’Ivoire through a study within RESAFIG union (Renouveau syndical des agents des Finances générales). It specifically shows, through the prism of the theory of organisational legitimacy, that the internal and external constraints of the union induce the maintenance of the physical vote, despite the fact that this technique produces a low rate of electoral participation and a democratic backlash. On this basis, the analysis concludes, on the one hand, that the satisfaction by the union leaders of the socio-corporatist expectations of the union members is the source legitimising the bypassing of electronic voting. On the other hand, union leaders intimidated and punished by the state because of corporatist demands indirectly phagocytise the political engagement of union members, which reflects their indifference to the maintain physical vote.